Exploring and validating hub genes associated with atopic dermatitis through weighted gene co-expression network analysis and machine learning - Yu Miao; Aoxue Wang (Medicine, 2026)
This study aimed to identify novel biomarkers of atopic dermatitis (AD) and investigate their pathogenic mechanisms. We analyzed 7 AD-related datasets from the gene expression omnibus database and identified overlapping differentially expressed genes through integrated analysis of differential expression and weighted gene co-expression networks. Functional enrichment analysis revealed that these genes were primarily associated with skin development and keratinization. Using the least absolute shrinkage and selection operator and support vector machine recursive feature elimination, we further refined the candidate biomarkers to 6 key genes (betacellulin, C1orf68, cytochrome p450 family 2 subfamily J member 2, family with sequence similarity 234 member B, insulin-like growth factor like family member 2, and whey acidic protein 4-disulfide core domain 12). Immune infiltration analysis using CIBERSORT revealed significant correlations between these hub genes and specific immune cells. Single-cell RNA sequencing analysis revealed that these genes were predominantly expressed in endothelial cells and keratinocytes. Subsequent validation using an independent cohort confirmed distinct expression dysregulation: 5 genes (betacellulin, C1orf68, cytochrome p450 family 2 subfamily J member 2, family with sequence similarity 234 member B, and insulin-like growth factor like family member 2) were downregulated, whereas whey acidic protein 4-disulfide core domain 12 was significantly upregulated in AD samples. These findings not only provide novel mechanistic insights into AD pathogenesis but also identify promising therapeutic targets for future research.